Pedal Exercise Machine For Physical Rehabilitation Of Stroke Patients - Amin, Ahmad Bulya Md (Universiti Sains Malaysia, 2019)
Stroke recovery is an important field in modern world, and many researcher and scientist have worked hard to obtain the best recovery method. One of the most common method for stroke recovery is through aerobic exercise such as walking, running, swimming, or cycling. In this research the focus of stroke recovery is focus on cycling exercise. The common cycling exercise product that is available in the market is usually only for a single limb. The problem with this product is that during rehabilitation only a single limb that can train for recovery at a time. This causes a patient to spend extra hours to rehab the other limb therefore by designing a product that could accommodate both limbs at the same time would greatly improve the time needed for recovery process. The next problem that the stroke patient face is the problem of fatigue, whenever during the rehab the patient tends to be fatigued due to longer rehab process, hence the designed product also able to accommodate passive activity where a motor is used to run the designed product so that the amount of muscle activity is maintain throughout the rehabilitation process. An experiment is carried out on two healthy subjects using a fabricated product and a market product. A paired T-test calculation is used to measure the difference between the two products in EMG reading. At the end of the experiment the significant value between the market product and the fabricated product when the fabricated in active mode with of both limbs being engaged and the P-value obtained is 0.003 for the right side and 0.032 for the left side which are significantly better compare to market product. The highest average reading is also obtained when using the fabricated product in active mode while engage both limbs with the highest average of the right side upper limb is 43.94 μV and right side lower limb is 38.19 μV. hence from the research it can be deduced that by using the fabricated product, the stroke patient can have higher muscle output than the one available in the market. For future work, more number of subjects should be choose in order to have accurate results and to validate the reliability of the fabricated product.